Multifunctional novel Diallyl disulfide (DADS) derivatives with β-amyloid-reducing, cholinergic, antioxidant and metal chelating properties for the treatment of Alzheimer's disease. Issue 19 (1st October 2015) - Manral, Apra; Saini, Vikas; Meena, Poonam; Tiwari, Manisha
Graphical abstract: Abstract: A series of novel Diallyl disulfide (DADS) derivatives were designed, synthesized and evaluated as chemical agents, which target and modulate multiple facets of Alzheimer's disease (AD). The results showed that the target compounds5a –l and7e –m exhibited significant anti-Aβ aggregation activity, considerable acetylcholinesterase (AChE) inhibition, high selectivity towards AChE over butyrylcholinesterase (BuChE), potential antioxidant and metal chelating activities. Specifically, compounds7k and7l exhibited highest potency towards self-induced Aβ aggregation (74% and 71.4%, 25 μM) and metal chelating ability. Furthermore, compounds7k and7l disaggregated Aβ fibrils generated by Cu 2+ -induced Aβ aggregation by 80.9% and 78.5%, later confirmed by transmission electron microscope (TEM) analysis. Besides, 7k and7l had the strongest AChE inhibitory activity with IC50 values of 0.056 μM and 0.121 μM, respectively. Furthermore, molecular modelling studies showed that these compounds were capable of binding simultaneously to catalytic active site (CAS) and peripheral anionic site (PAS) of AChE. All the target compounds displayed moderate to excellent antioxidant activity with ORAC-FL values in the range 0.546–5.86 Trolox equivalents. In addition, absorption, distribution, metabolism and excretion (ADME) profile and toxicity prediction (TOPKAT) of best compounds7k and7l revealed that they have drug like properties and possess very low toxic effects. Collectively, the results strongly support our assertion that these compounds could provide good templates for developing new multifunctional agents for AD treatment.